2022
DOI: 10.1093/ejcts/ezac164
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker implantation after sutureless or stented valve: results from a controlled randomized trial

Abstract: OBJECTIVES Sutureless aortic valves demonstrated non-inferiority to standard stented valves for major cardiovascular and cerebral events at 1 year after aortic valve replacement. We aim to assess the factors correlating with permanent pacemaker implantation (PPI) in both cohorts. METHODS PERSIST-AVR is a prospective, randomized, open-label trial. Patients undergoing aortic valve replacement were randomized to receive a suture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The results showed a decreased pacemaker rate and improved hemodynamics, confirming the importance of avoiding oversizing, which is crucial for the best hemodynamic and clinical outcomes with the Perceval valve. This is also in line with the lowest incidence of permanent pacemaker implantation observed in this series compared to other published experiences [11,23]. The reason behind this positive trend may be related to the improved design of Perceval PLUS, featuring a reduced sub annular valve collar protrusion in the size XL.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results showed a decreased pacemaker rate and improved hemodynamics, confirming the importance of avoiding oversizing, which is crucial for the best hemodynamic and clinical outcomes with the Perceval valve. This is also in line with the lowest incidence of permanent pacemaker implantation observed in this series compared to other published experiences [11,23]. The reason behind this positive trend may be related to the improved design of Perceval PLUS, featuring a reduced sub annular valve collar protrusion in the size XL.…”
Section: Discussionsupporting
confidence: 89%
“…The reason behind this positive trend may be related to the improved design of Perceval PLUS, featuring a reduced sub annular valve collar protrusion in the size XL. While in the previous publications with Perceval the use of a valve size XL was an independent predictor of postoperative permanent pacemaker implant [23], in this preliminary experience the incidence of PPI with valve size XL was comparable to other valve sizes (4.5% size XL vs 4.6%, 5.1% and 2.0% with size S, M and L, respectively), suggesting the positive impact of the new design on this size.…”
Section: Discussionsupporting
confidence: 42%
“… 22 An additional subanalysis of this trial by Lorusso et al analyzed the influence of prosthesis size on PPI rates and determined that increased rates of PPI following SUAVR came only with implantation of the extra-large device. 88 The results of multiple large retrospective, propensity-matched analyses are largely consistent with these results. 89 , 90 Superior results in various measures of postoperative morbidity, including bleeding, ICU and hospital LOS, low cardiac output syndrome, atrial fibrillation, and mild aortic regurgitation have also been noted following SUAVR.…”
Section: Resultssupporting
confidence: 57%
“…Also, the technique of valve deployment during TAVI is related to the frequency of PPI and was found to be greater in the group of early-generation self-expanding compared to balloon-expandable valves [ 5 ]. It has been demonstrated that the implantation of a sutureless/rapid-deployment (SURD) aortic valve prosthesis is related to higher PPI rate in comparison to a stent-sutured bioprosthesis (SAVR) [ 6 ]. Furthermore, the frequency of intraventricular conduction abnormalities, such as left (LBBB) and right bundle branch blocks (RBBB), is increased with prosthetic aortic valve implantation.…”
Section: Introductionmentioning
confidence: 99%